#### Answer

$y'= 6x-2-2e^{-2x}$

#### Work Step by Step

$y = 3x^2-2x+e^{-2x}$
Using Power Rule and $\frac{d}{dx}e^{nx}$ = $ne^{nx}$:
$y'=3(2)x^{(2-1)} - 2(1)x^{(1-1)}+(-2)e^{-2x} = 6x-2-2e^{-2x}$

Published by
Pearson

ISBN 10:
0321947347

ISBN 13:
978-0-32194-734-5

$y'= 6x-2-2e^{-2x}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.